POLITIK HUKUM KEKUASAAN KEHAKIMAN - Rukiah Latuconsina (TAHKIM, 2017)
Law politics of judicial power is independent of state power to administer justice, uphold the law, and justice based on Pancasila, for the implementation of the legal state of the Republic of Indonesia. Political law judicial authority in Indonesia pre greatly influenced the 1945 amendment authoritarian government policies, both at government era of the Old Order and the New Order era. Because the government of the Old Order and New Order ruler held by the interpretation of the 1945 Constitution the judicial authority law Politics after the 1945 amendment to experience a positive change with the passage of several Judicial Power Act an independent, self-sufficient and free from intervention and pressure the authorities. So that the judicial authority (judges) can carry out its duties decide a case fairly and wisely. Keywords: legal political, judicial power